2011
DOI: 10.1007/s12253-011-9467-7
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Thymosin Beta 10 and AKAP13 Genes in Metastatic and Aggressive Papillary Thyroid Carcinomas

Abstract: Papillary thyroid carcinoma (PTC) is the most common well-differentiated thyroid cancer. Although the great majority of the cases exhibit an indolent clinical course, some of them develop local invasion with distant metastasis, and a few cases transform into undifferentiated/anaplastic thyroid carcinoma with a rapidly lethal course. To identify gene copy number alterations predictive of metastatic potential or aggressive transformation, array-based comparative genomic hybridization (CGH-array) was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The role of TMSB10 in cancer is mainly related to cytoskeletal alterations. TMSB10 is part of a gene expression signature for predicting lymph node metastasis of early stage cervical carcinomas (29) and is up-regulated in metastatic papillary thyroid carcinomas (30). The roles of STMN1 and TMSB10 in breast cancer metastasis are supported by their correlation and clustering with other metastasis-associated gene products within G1 metastasis related cluster 2, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TMSB10 in cancer is mainly related to cytoskeletal alterations. TMSB10 is part of a gene expression signature for predicting lymph node metastasis of early stage cervical carcinomas (29) and is up-regulated in metastatic papillary thyroid carcinomas (30). The roles of STMN1 and TMSB10 in breast cancer metastasis are supported by their correlation and clustering with other metastasis-associated gene products within G1 metastasis related cluster 2, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, Tbeta10 stimulates secretion of proinflammatory cytokines interleukin (IL-7) and IL-8, which may promote pancreatic cancer pathogenesis and progression [26]. Studies on thyroid carcinoma, melanoma, non-small cell lung cancer and some other malignant tumors [21,27,28] also show that Tbeta10 possesses tumor progression properties. In the present study, we demonstrated that high expression of Tbeta10 was associated with advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Tβ10 has been shown to confer cell migratory advantage in thyroid carcinoma [17,18,35,36], and melanoma [19,31,37]; but disadvantage in endothelial cells [38] and ovarian cancer [24]. However, roles of Tβ10 in cancer development such as cell growth and apoptosis still remain controversial among cancers [15,16].…”
Section: Discussionmentioning
confidence: 99%